The fantasy of reality : on the design drawings of Álvaro Siza Vieira - Duarte, João Miguel Couto, 1966- (2019)
Intelligence, creativity and fantasy / Proceedings of the 5th International Multidisciplinary Congress; coordenação de Mário S. Ming Kong, Maria do Rosário Monteiro, Maria João Pereira Neto. - Londres : CRC Press, 2019. - P. 137-142.